Isolation and Molecular Identification of Direct Red 80 Synthetic Dye Degradation Bacteria from Palembang Indonesia Jumputan Cloth Industrial Waste - Muharni; Elisa Nurnawati; Heni Yohandini; Hary Widjajanti (Science and Technology Indonesia, 2023)
Industrial waste from Jumputan cloth production pose a significant risk to environmental safety due to their toxic synthetic dye content. Several studies have shown that the presence of bacteria in these materials plays a very important role in decolorization process of the constituent dye. Therefore, this study aims to isolate bacteria with the ability to decolorize direct red 80 from Jumputan cloth industrial waste. Characterization of isolates was carried out macroscopically, microscopically, and biochemically, followed by molecular identification using the 16S rRNA gene. Decolorization effects of the samples on red dye 80 were then assessed using a spectrophotometer at a maximum wavelength of 528 nm. The results showed that 6 bacteria isolates can degrade dye, with decolorizing power ranging from 26.33±0.94 - 73.67±0.47. The highest potential for decolorizing waste synthetic dye is seen in isolate BD 05. Phylogenetic analysis showed that there were 3 genera of bacteria among the samples obtained, namely Bacillus, Aeromonas, and Pseudomonas. These bacteria were closely related to Bacillus tropicus, Areomonas jandaei, and Pseudomonas stutzeri. Pseudomonas stutzeri (BD 05) has the highest potential in handling jumputan industrial waste.